SPEED SENSOR FAULT DETECTION AND DIAGNOSIS OF INDUCTION MOTOR USING FUZZY BASED FAULT TOLERANT ALGORITHM (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This paper presents a three phase squirrel cage induction motor operates using indirect field control is used and speed sensor fault is diagnosis by fuzzy logic control. Induction motors are highly reliable, they are susceptible to many types of faults that can became catastrophic and cause production shutdowns, personal injuries, and waste of raw material. Induction motor faults can be detected in an initial stage in order to prevent the complete failure of the system and unexpected production costs. So,new fault tolerant algorithm is used to detect the faults and  diagnosis the fault, with the help of current estimated and speed estimated blocks. Fault tolerant algorithm was used for diagnosis current and speed sensor faults.Here, IFOC techniques is used to control the switches of the inverter and system performance is analysed. Estimated current control block is used to diagnosis  speed and  current sensor  which is estimated by logic based decision algorithm. In this paper modeling and simulation of three phase induction motor was deceloped using IFOC and fuzzy based new fault tolerant algorithm is also developed by using MATLAB/SIMULINK software.